Imidazoles and imidazole metabolism - Trout, G. E. (My University, 1966)
Only a small number of compounds containing the imidazole ring are found in living systems, but most of these possess marked biological activity. The amino acid histidine and its decarboxylation product, histamine, are universally distributed. Histidine is not only a constituent of nearly all proteins, but in the dipeptide carnosine (alanylhistidine) plays an important part in muscle biochemistry.
Thesis submitted for the degree of Doctor of Philosophy at the University of the Witwatersrand, Johannesburg, South Africa.
Keywords: Imidazoles; Imidazoles/metabolism